2014
DOI: 10.1002/mabi.201300576
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Poly(Vinyl Amine)s Bearing Azetidinium Groups: One Pot Preparation in Water and Antimicrobial Properties

Abstract: A simple, robust one pot procedure for the preparation of waterborne multifunctional poly(vinyl amine)s (PVAms) is presented. By post-polymerization modification of PVAm with a bifunctional coupler and functional couplers cationic, reactive azetidinium groups, and alkyl chains are introduced in the side chains of PVAms. The structure-activity relations (effect of hydrophobic and cationic modifications) of these antimicrobial polymers are studied; the minimum inhibitory concentration (MIC) against both (Gram po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Polymers with cations directly attached to the hydrophobe were more effective against bacteria, compared to segregated polymers and polymers with cation and hydrophobe linked with an alkyl chain. In a more recent study, they synthesized azetidinium functionalized poly(vinyl amine) copolymers (Table 1D) via a one-pot post-polymerization modification approach using suitable functional couplers [72]. When the hexyl chain in the hydrophobic group was replaced by a decyl chain, antimicrobial activity against S. aureus and Escherichia coli increased significantly.…”
Section: Random Copolymersmentioning
confidence: 98%
“…Polymers with cations directly attached to the hydrophobe were more effective against bacteria, compared to segregated polymers and polymers with cation and hydrophobe linked with an alkyl chain. In a more recent study, they synthesized azetidinium functionalized poly(vinyl amine) copolymers (Table 1D) via a one-pot post-polymerization modification approach using suitable functional couplers [72]. When the hexyl chain in the hydrophobic group was replaced by a decyl chain, antimicrobial activity against S. aureus and Escherichia coli increased significantly.…”
Section: Random Copolymersmentioning
confidence: 98%
“…The microstructures containing the hydrophobic segment attached directly to the segment with cationic groups showed higher efficiency against bacteria than the one with cationic groups that are not attached to the alkyl chain [150]. Later, the same group tested multifunctional poly(vinyl amines) (PVAms), with cationic, reactive azetidinium and alkyl chain groups introduced in the side chains of PVAms, against bacteria (Figure 8) [151]. The antimicrobial efficacy of the polymers was improved by increasing the hydrophobic moiety, namely by replacing the hexyl group by the decyl group.…”
Section: Biocidal Polymersmentioning
confidence: 99%
“…In addition, a higher content of cationic groups has also led to a significant increase of the antimicrobial efficiency. The results suggested that the PVAms samples containing 11% of hydrophobic and 5%–14% of cationic groups presented the best antimicrobial efficacy [151]. …”
Section: Biocidal Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…To prepare polymer coated antimicrobial surfaces in the current work, we focused on the application of azetidinium functionalized polymers. The advantages of azetidinium groups in this application are: (a) inhibition of bacterial growth via interaction with cell components due to the cationic nature of this group [15,16] and (b) improving the adhesion via both (i) ionic interaction and (ii) covalent linkage. The four membered rings attached to the polymers react with the functional groups on the surface forming covalent bonds [17].…”
Section: Introductionmentioning
confidence: 99%